Landscape Optimization Design based on the Concept of "Ming Tang" in Geomancy Science - Yang Zhou; Azhari Md Hashim; Guo Che (Environment-Behaviour Proceedings Journal, 2025)
This paper discusses the application of the concept of "Ming Tang" in modern landscape optimization in Chinese geomancy science. Through literature review and case analysis, the application principles of this concept in modern landscape design are extracted, and the project is implemented. It is found that the concept of "Ming Tang" can guide the order of environmental space, increase cultural significance, optimize functional layout, and improve comfort. In addition, this paper also discusses the limitations of the concept of "Ming Tang" in modern landscape design, such as lack of quantitative data support, cultural background differences, etc.